Cancers missed, women dismissed yet persist: natural language processing of online forums - Kathleene T. Ulanday; Maxim Topaz; Jeanette Shekelle; Marley Gibbons; Desiree Walker; Paula M. Castaño; Amanda Nixon; Stacy Lewis; Mary Beth Terry; Lauren C. Houghton (Breast Cancer Research)
Abstract Objective To identify gaps and delays in the detection of early onset cancer. Methods We examined firsthand experiences shared on an online discussion board hosted by the Young Survival Coalition—an advocacy group for young adults diagnosed with breast cancer—spanning the years 2009 to 2019. We used natural language processing to detect codes: “first signs and symptoms,” “steps to diagnosis,” “healthcare interactions,” “patient-provider-system feelings,” and “staging/type.” In the training dataset, we used qualitative content analysis to code text from 750 of the forum’s 571,914 posts. We developed and evaluated automated approaches to quantify the proportion of codes in all posts. Lastly, we qualitatively reviewed the classified posts to identify areas for improvement along the clinical pathway. Results The vast majority (81%) of young adults self-detected their breast cancer rather than the cancer being detected through a clinical breast exam. Young adults (70%) were dissatisfied with their care because they encountered delays at three crossroads along the clinical pathway: 1) whether the clinician ordered tests or dismissed the individual as too young; 2) whether imaging modalities were sensitive or not; 3) whether a biopsy confirmed or missed the cancer. Mental health challenges and parenting pressures compounded these delays. True positive cases who experienced these delays strongly encouraged their peers to self-advocate, persist and insist on further testing until diagnosed accurately. Conclusion Dismissal and delays in diagnosis of early onset breast cancer mean potentially worse prognosis since later stage cancers are more aggressive with fewer treatment options. The perspectives from survivors highlight the need for more research informing early detection in young adults by considering breast awareness, use of MRI and ultrasound, biopsy referrals for exhibited breast symptoms in the absence of positive imaging, and sociomedical support for individuals in their role as current or future parent.